Problem Solving, Skills and Academic Performance when Teaching Mathematics - Gamarra Astuhuaman, Guillermo (2020)
This article shares the results of a study among 115 university students enrolled in a Mathematical Logic II course. The objective of this study was to determine if problem-solving methods influence cognitive skills development and help improve academic performance in a group of university students. The students were divided into two groups- the Experimental Group (EG) and the Control Group (CG) and were administered two knowledge tests – a pre-test and post-test. After the Experimental Group took the pre-test, they were taught the problem-solving method during 16 weeks. Upon completion of the course content, the students took a post-test. The collected data collected includes the grades from these assessments which were evaluated both qualitatively and quantitatively and analyzed through descriptive and inferential statistics. The pre-test and post-test mean scores for both groups was 11.25 (GE) and 11.64 (GC); and 15.08 (GE) and 11.42 (GC), respectively. Regarding the qualitative aspect, although the experimental group improved its calculation, variable identification, strategy design, deduction and inference skills, it did not reveal a significant improvement. An inferential analysis reveals a Pearson's coefficient equal to 0.771 and with a p-value of 0.000, thus proving the impact of using the applied method on cognitive skills development and improved academic performance.